Chitosan-Tricarbocyanine-Based Nanogels Were Able to Cross the Blood–Brain Barrier Showing Its Potential as a Targeted Site Delivery Agent - Rivera López, Emilio (2024)
Targeting drugs to the central nervous system (CNS) is challenging due to the presence of the blood–brain barrier (BBB). The cutting edge in nanotechnology generates optimism to overcome the growing challenges in biomedical sciences through the effective engineering of nanogels. The primary objective of the present report was to develop and characterize a biocompatible natural chitosan (CS)-based NG that can be tracked thanks to the tricarbocyanine (CNN) fluorescent probe addition on the biopolymer backbone. FTIR shed light on the chemical groups involved in the CS and CNN interactions and between CNN-CS and tripolyphosphate, the cross-linking agent. Both in vitro and in vivo experiments were carried out to determine if CS-NGs can be utilized as therapeutic delivery vehicles directed towards the brain. An ionic gelation method was chosen to generate cationic CNN-CS-NG. DLS and TEM confirmed that these entities’ sizes fell into the nanoscale. CNN-CS-NG was found to be non-cytotoxic, as determined in the SH-SY5Y neuroblastoma cell line through biocompatibility assays. After cellular internalization, the occurrence of an endo-lysosomal escape (a crucial event for an efficient drug delivery) of CNN-CS-NG was detected. Furthermore, CNN-CS-NG administered intraperitoneally to female CF-1 mice were detected in different brain regions after 2 h of administration, using fluorescence microscopy. To conclude, the obtained findings in the present report can be useful in the field of neuro-nanomedicine when designing drug vehicles with the purpose of delivering drugs to the CNS.